Remote Instrumentation and Virtual Laboratories Service Architecture and Networking - Davoli, Franco.; Davoli, Franco.; Meyer, Norbert.; Meyer, Norbert.; Pugliese, Roberto.; Pugliese, Roberto.; Zappatore, Sandro.; Zappatore, Sandro. (Springer US : Imprint: Springer, 2010)
Remote Instrumentation and Virtual Laboratories focuses on all aspects related to the effective exploitation of remote instrumentation; on making instrumentation fully integrated into the e-Science scenario by considering middleware, networking, and metrological aspects; and the building of complex virtual laboratories on top of real devices and infrastructures. These include SOA and related middleware, high-speed networking in support of Grid applications, wireless Grids for acquisition devices and sensor networks, Quality of Service (QoS) provisioning for real-time control, measurement instrumentation and methodology, as well as metrology issues in distributed systems. The activities generally termed "e-Science" encompass a wide range of scientific disciplines. It is characterized by highly intensive computation on huge data sets in a large-scale distributed environment, by the real-time interaction and collaboration among many scientists working on a specific problem or data set worldwide, and by the use of specific instrumentation—the pieces of equipment physically producing the data that pertain to a certain experiment. In addition to remote instrumentation, this book also addresses new challenges that will arise from wireless access, wireless sensor networks, and the traversal of heterogeneous network domains.